The hardy-littlewood inequality for the solution to P-Harmonic Type System - Cao, Zhen-Hua; Bao, Ge-Jun; Li, Rong-Lu; Guo, Li-Feng; Ling, Yi (Tamsui Oxford Journal of Mathematical Sciences)
Hardy-Littlewood inequality is instrumental in virtually all analytic aspects of the theory of partial differential equations, linear and nonlinear. And conjugate A-harmonic tensors, the solutions to conjugate A-harmonic equation, are generalizations of conjugate harmonic functions to differential forms. In this paper, we shall prove the Hardy-Littlewood inequality for the p-harmonic type system which is nonhomogeneous conjugate A-harmonic equation.